Manajemen Pengembangan Objek Wisata Paralyang wayu di Dinas Pariwisata Kabupaten Sigi - rijal, andi bua alya mangkawani; Nasir Mangasing; Andi Maman Firmansyah (JPS: Journal of Publicness Studies, 2024)
This study aims to analyze and find out what actions the Sigi Regency Tourism Departmen has taken in developing the Wayu Paragliding Tourism Object. The research method used in this research is qualitative research method. The research location is at the Sigi Regency Tourism Departmen Office. In this study, the analysis used G.R Terry's theory states 4 management concepts (POAC) including planning, organizing, actuating, controlling. The number of informants in this study were 6 people. Data analysis used Miles and Huburman.The results of research in the field that the development of the Wayu Paragliding Tourism Object by the Sigi Regency Tourism Department, in the planning aspect, on facilities - infrastructure to continue paving, procurement of street lights, road dividers, directions, repair of damaged facilities and provision of clean water. And finally update the RIPPARDA so that the planning of the Sigi Regency Tourism Office runs well. In the organizing aspect, it has gone well, but there are still many things that must be improved and developed, especially in adding and improving facilities, as well as involving more groups that have a positive impact on the wayu paragliding tourist attraction.The actuating aspect is the lack of discipline of the Tourism Office towards employees, as well as the cleanliness around tourist attractions that are scattered by garbage due to the lack of human resources that help officers in terms of cleaning the tourist attraction area.